PENGARUH MOTIVASI DAN BUDAYA KERJA TERHADAP KINERJA PEGAWAI KANTOR KECAMATAN CILEDUG KOTA TANGERANG - Fahmi Husaini; Styo Budi Utomo (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the influence of motivation and work culture on employee performance at the Ciledug District Office, Tangerang City. Using Quantitative methods. The population of this study was 60 respondents. The research results show that Motivation (X1) has a positive and significant effect on employee performance with the regression equation Y = 20.745+0.489 X1. The correlation value is 0.616, this value has a strong level of relationship. The coefficient of determination value of the motivation variable influences employee performance variables by 38%, while the remaining 62% is influenced by other factors. And the results of the hypothesis test (t test) obtained a tcount value of 5.962 > ttable 1.672 and a significance of 0.000<0.05 Work culture (X2) has a positive and significant effect on employee performance with the regression equation Y = 22.876+0.434 X2, a correlation value of 0.621, this value has a strong level of relationship. The coefficient of determination for the work culture variable influences the performance variable by 38.6%, while the remaining 61.4% is influenced by other factors. And the results of the hypothesis test (t test) obtained a t value of 6.040 > t table 1.672 and a significance of 0.000 < 0.05. Motivation (X1) and Work Culture (X2) simultaneously have a significant effect on employee performance with the regression equation Y = 17.825 + 0.293 X1 + 0.268 The coefficient of determination value simultaneously states that the motivation variable is 46.5% while the remaining 53.5% is influenced by other factors. And the results of the hypothesis test (F Test) obtained an Fcount value of (24.808>3.16) and a significance of 0.000<0.05. So a decision can be made that Ho3 is rejected and Ha3 is accepted, meaning that there is an influence of Motivation and Work Culture on the Performance of Ciledug District Office Employees, Tangerang City.